Architektur als Markenkommunikation : Dynaform und Cube. - Brauer, Gernot, ....- (Basel : Birkhäuser, 2002)
Samenvatting:What can innovative, highly experimental and brand oriented architectureachieve today? The answers here are formulated by architects,construction engineers and marketing experts using two examples from theInternational Motor Show, Frankfurt.For some years the architecture of buildings has been discovered as apotential form of brand communication. The automobile industry inparticular has made use of such "communicative" architecture to giveexpression to brand image. This book investigates the underlying conceptsand processes by examining the pavilions of two makes of car - BMW andthe Mini- - at the International Motor Show in Frankfurt. Theirpavilions, Dynaform + Cube were designed using High-End software tocreate free-form shapes. The realisation of these forms proved highlychallenging, but just a few years ago such utopian designs would havebeen considered impossible to build.Eighteen authors have contributed generously illustrated reports;architects and engineers have shed light on the plans, structures, theconstruction, and also on the less tangible furnishings such as thefilms; marketing experts explain the significance of architecture inbrand communication. With in excess of 600 colour illustrations and anaccompanying CD Rom containing video sequences from the projects, thispublication will be of interest to readers active in architecture, theconstruction industry and marketing
Teksten in het Duits en het Engels.
Keywords: Architectuur; Beeldvorming; Gebouwen; Ondernemingen